Writing, Interpreting Fiction in South Africa: The Last 30 Years. Issue 1 (2nd January 2022) - Chapman, Michael
Abstract : Responding to the theme of this issue, 'The Last 30 Years: Looking Back, Going Forward', the article assesses the work of several writers of fiction who have garnered attention in both South African-based literary journals and literary journals abroad: Vladislavić, Wicomb, Van Niekerk, Krog, Mda, and, under the grouping '"A Tumultuous Urbanism", and More', Mhlongo, Mpe, Duiker, Galgut, Beukes, and Matlwa as well as others of briefer reference. The fiction is considered in relation to the predominant interpretative frame of the last thirty years: namely, the 'postcolonial'.